2019
DOI: 10.1111/jon.12602
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transcranial Doppler Monitoring in Patients with Multi‐Territory Acute Embolic Strokes: A Review

Abstract: Acute multi‐territory, embolic cerebral infarctions are often associated with serious underlying clinical conditions including the presence of highly “active” emboligenic sources causing that in turn may result in high early recurrence rates. Prompt diagnosis, risk stratification, and treatment are substantial for the prevention of subsequent embolization that would result in further clinical deterioration. Among other clinical investigations, transcranial Doppler (TCD) monitoring is highly efficacious for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 169 publications
(293 reference statements)
0
24
0
1
Order By: Relevance
“…72 Another diagnostic tool aiming on the assessment of the effect of secondary prevention and risk of recurrent embolization in patients with endocarditis, is micro-emboli detection. 73 Several studies showed that intravenous thrombolysis for ACI related to endocarditis is associated with higher rates of ICH and worse outcome. 74,75 The treatment is in the first line based on management of the underlying disease in both IE and NBTE.…”
Section: Aortic Embolismmentioning
confidence: 99%
See 2 more Smart Citations
“…72 Another diagnostic tool aiming on the assessment of the effect of secondary prevention and risk of recurrent embolization in patients with endocarditis, is micro-emboli detection. 73 Several studies showed that intravenous thrombolysis for ACI related to endocarditis is associated with higher rates of ICH and worse outcome. 74,75 The treatment is in the first line based on management of the underlying disease in both IE and NBTE.…”
Section: Aortic Embolismmentioning
confidence: 99%
“…Microemboli detection should be used more extensively in patients with MACI in order to avoid a negative progression and to assess the effect and possibly adjust the strategy of secondary prevention of recurrent stroke. 73…”
Section: Microemboli Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…84 Therefore, detection of MES early post-reperfusion may prompt the administration of more potent antithrombotic therapies to reduce risk of stroke recurrence. 85 Absence of recanalization after IVT treatment for LVO-associated AIS increases risk of not only sICH but also of malignant edema development with a subsequent increase of intracranial pressure (ICP). The Systemic thrombolysis in patients with acute ischemic stroke and Internal Carotid ARtery Occlusion study demonstrated that, although IVT increased odds of favorable outcome (adjusted odds ratio: 1.80; 95% CI: 1.03-3.15; p=0.037), it also increased rates of malignant edema (8.3% vs. 3.1%).…”
Section: Tcd/tccd Applications In the Prognosis Of Clinical Outcomes mentioning
confidence: 99%
“…La presencia de placas de ateroma en el arco aórtico cuadriplica la incidencia de stroke, que se caracteriza por lesiones isquémicas múltiples en diferentes territorios vasculares. Independientemente del procedimiento quirúrgico, los pacientes con placas de ateroma mayores de 4 mm tienen una incidencia anual de stroke recurrente del 12% (41) .…”
Section: Prevención Intraquirúrgicaunclassified